Kinerja Kolektor Pemanas Air Tenaga Surya Menggunakan Bekas Kaleng Minuman Sebagai Absorber Dengan Air Yang Bersirkulasi Pada Pembukaan Katup 30o - Eigko Malau; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Nowadays, hot water is widely used for bath. For produce hot water, people usually use furnace to boil the water and other use an electricity to heat the water. Research in solar water heater can be the alternative to get hot water without using fossil fuels, replace the furnace and water that used electricity. In this study the solar collector was made the beverage cans as the absorber. The purposes of this study was to achieve the value of efficiency of solar collector and temperature of water at the outlet of storage tank, which the water circulation and a valve were opened at 30o. The dimensions of solar water heater were 2.3 meter in length, 0.8 meter in width and 1.8 meter in height and its volume of 127 L. The solar collector was placed at outside of laboratory Universitas Riau for 9 hours. The data taken from the testing were the temperature of absorber, flow rate, light intensity and temperature of water inlet and outlet. The result of this study showed the second day of the experiment, that was a better efficiency with 34.5%. Whilst, the highest temperature of water circulation was 44.9oC that was occurred in the first day.Keywords: Absorber, Solar Water Heaters, Collector.